2012
DOI: 10.7860/jcdr/2012/4168.2575
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Retrograde Peri-Implantitis: A Case Report

Abstract: Peri-Implantitis is defined as an inflammatory reaction with the loss of the supporting bone in the tissues which surround a functioning implant. The peri-implantitis lesions are often asymptomatic and they are usually detected during the routine recall appointments. Careful probing around the teeth and the implants should be done routinely along with the radiologic evaluation during these check-up appointments. Retrograde peri-implantitis may sometimes prove even more difficult to identify, resulting in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…Presentation of fistula and radiographic lesion at implant apex was observed in 15 of 20 studies 20,24,28‐33,35,36,38,41‐44 . Four of 20 studies reported that only radiographic evidence of lesion was apparent, with no clinical signs of infection or inflammation 27,34,39,45 . In a case series of six patients, in which lesion had quicker onset compared with other case reports, clinical presentation was buccal or facial abscess with intense pain 33 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Presentation of fistula and radiographic lesion at implant apex was observed in 15 of 20 studies 20,24,28‐33,35,36,38,41‐44 . Four of 20 studies reported that only radiographic evidence of lesion was apparent, with no clinical signs of infection or inflammation 27,34,39,45 . In a case series of six patients, in which lesion had quicker onset compared with other case reports, clinical presentation was buccal or facial abscess with intense pain 33 …”
Section: Resultsmentioning
confidence: 98%
“…On the basis of case reports analyzed, RPI was diagnosed between 1 week and 4 years after implant placement 26 , 28 . Thirteen studies reported that RPI lesions were diagnosed within 6 months after implant placement 20,24,27‐44 . Predominant diagnostic presentation of lesion was presence of fistula at buccal or facial abscess of apical portion of implant, and subsequent periapical radiographs taken demonstrated radiolucent lesion.…”
Section: Resultsmentioning
confidence: 99%
“…13,14,18,19,21 The prognosis can be considered fair to good. The resolution frequency of class III lesions is lower than that of class I and II lesions.…”
Section: Discussionmentioning
confidence: 99%
“…When the lesions belonged to class III at the time of diagnosis, the management is frequently more aggressive including open-flap debridement, bone graft, and barrier membrane placement and/or resection of the apical part of the implant. 7,13,14,18,51 If the lesion does not resolve or the implant is clinically mobile, the implant has to be explanted. 36,42,54,55 There are also reports of successful implant placement after explantation at the same site.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha sugerido que el origen de esta lesión es a partir de microorganismos presentes en el alveolo durante la cicatrización o bien por lesiones periapicales en dientes adyacentes, de igual forma se ha sugerido que los microorganismos pueden reactivarse en el procedimiento quirúrgico durante la colocación del implante (Mohamed et al, 2012), por lo que se hace obligatorio el realizar un examen clínico minucioso que lleve a detectar los futuros focos de infección y así evitar el desarrollo de la periimplantitis retrograda o apical.…”
Section: Introduccionunclassified